A NEW SPECIES of THE FEATHER MITE GENUS COTINGODECTES and A NEW GENUS of PTERODECTINAE (ASTIGMATA: PROCTOPHYLLODIDAE) - Valim, Michel P.; Hernandes, Fabio Akashi [UNESP] (Taylor & Francis Inc, 2009)
In this paper a second species of the feather mite genus Cotingodectes Valim and Hernandes, C. breviphallus n. sp., is described from Rupicola rupicola (Passeriformes, Cotingidae) in Brazil. A new genus, Berladectes, is erected to accommodate Dolichodectes neotropicus Hernandes and Valim.
Keywords: Astigmata; Proctophyllodidae; Cotingodectes; feather mite; Systematics